Implications of Warm Temperatures and an Unusual Rain Event for the Survival of Ringed Seals on the Coast of Southeastern Baffin Island - Stirling, Ian; Smith, Thomas G. (ARCTIC, 2004)
We recorded an unusually warm period in early April 1979 along the coastline at the end of the Hall Peninsula on southeastern Baffin Island, Nunavut. Maximum temperatures remained at or above freezing for almost a week, and rain fell on our field camp on three consecutive days. In contrast, meteorological data collected from three nearby coastal stations (Brevoort Island, Cape Dyer, and Resolution Island) between 1950 and 1992 indicated that the mean minimum and maximum air temperatures for the month of April are normally 10-20°C cooler than the averages we recorded at our camp. Periodic warming to near freezing, probably due to the maritime influence of nearby open water in Davis Strait, occurs in this area in late March and early April, but not usually to the degree we observed. Between 1950 and 1992, additional similar rain events were recorded only twice at the coastal weather stations. In late March, we found slumped roofs over some ringed seal (Phoca hispida) birth lairs and others that had collapsed, probably because of four days of weather only slightly below freezing and heat generated by seals within the lairs. After the rain in April, we found subnivean lairs with melted roofs, and several snowdrifts that had previously contained lairs were completely washed away. Newborn pups were left lying on the bare ice, subject to thermoregulatory stress and vulnerable to significantly increased predation by polar bears (Ursus maritimus) and arctic foxes (Alopex lagopus). If the climate continues to warm in the Arctic, as is predicted, it is likely that rain will be more widespread during early spring. If that occurs, the premature removal of protection offered by subnivean birth lairs may expose young ringed seal pups to high levels of predation, which may negatively affect populations of ringed seals and the polar bears that depend on them for food. Au début d'avril 1979, on a enregistré une période anormalement tempérée le long du littoral aux confins de la péninsule Hall dans le sud-est de l'île Baffin, au ...